Analysis of the Influence of Internal Communication on the Work Culture of Outsourced Employees - Devina Salsabila Hidayat; Nadia Itona Siregar (Universitas Negeri Yogyakarta, 2025)
This study examines the phenomenon of information gaps, misunderstandings, and psychological alienation from organizational culture experienced by outsourced employees due to their limited access to formal internal communication channels. This issue is evident at PT X, where the implementation of the “SOLUTION” work culture (Serve, Organized, Leading, Uniqueness, Totality, Innovative, Open-minded, and Networking) has not been fully internalized among outsourced employees. This condition is influenced by the limited frequency of work culture training programs, which are conducted only once a year, as well as the dominance of permanent employees in formal discussion forums. This study aims to analyze the influence of internal communication on the work culture of outsourced employees at PT X. A quantitative method with an explanatory approach was employed. Primary data were collected through structured questionnaires distributed to 32 outsourced employees with a minimum of two years of work experience, while secondary data were obtained through a literature review. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that internal communication has a positive and significant effect on employees’ understanding of work culture, as reflected by a P-value of 0.000 (< 0.05) and a path coefficient of 0.904. These results suggest that more effective internal communication contributes to a stronger understanding and internalization of organizational culture among outsourced employees. Furthermore, the R² value of 0.818 indicates that internal communication explains 81.8% of the variance in employees’ understanding of work culture, while the remaining 18.2% is influenced by other variables outside the scope of this study.